(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2019)
(Note: Herein the term, ‘Nepali Painting’ exclusively refers to the earlier art of Painting – rooted in religious faiths: and not the art that emerged after the arrival of western notion of painting.) For centuries, ‘The art of Painting in Nepal’ remained confined to the visual forms associated with spiritual beliefs: or as a description of imageries from Hindu and Buddhist pantheon. Occasionally, the visuals also narrated rise or decline of particular thoughts or a cult within a given time. The complexities found in the art also, have had intrigued many – by the impressive presence of myriad set of imageries – representing varied meanings or beliefs, expressed in diverse visual forms. But little is explained and argued on or about the underlining reasons or the deeper human desire to envision so. To argue on it or explain it, it remains a challenge. To dwell on it, it also becomes imperative to go behind - look to the earlier times when chosen thoughts were appeared first or impressed upon the early people. This is necessary so as to understand the state of mind and their perception of life then. Only then, one can or may imagine or analyze what may have had led them to the chosen beliefs and to the visual forms that we call art today. This should be described as the driving spirit of the art. Present essay therefore, is a brief and a modest attempt to unravel some of such driving spirits – based on the available references and also, personal observations.